Frequency-tunable Optoelectronic Oscillator With Synchronized Dual-Wavelength Narrow-Linewidth Laser Output - Guangcan Chen; Dan Lu; Song Liang; Lu Guo; Wu Zhao; Yongguang Huang; Lingjuan Zhao (IEEE Access, 2018)
Synchronized dual-wavelength narrow-linewidth lasers and a wideband frequency-tunable optoelectronic oscillator are simultaneously realized using mutual-injection-locked distributed feedback (DFB) lasers. The two laser modes serve as the seeding light and a microwave photonic filter for the optoelectronic oscillation. Mutual-injection locking between the two DFB lasers through a delay fiber loop results in synchronized narrow-linewidth operation. Microwave tuning from 19 to 41 GHz has been obtained through thermal-tuning of the DFB lasers, with the single-sideband phase noises below -100 dBc/Hz at a 10-kHz frequency offset from the carrier. Laser linewidth has been reduced from several-MHz to kHz with a linewidth reduction factor over 104.